Faktor-Faktor Yang Mempengaruhi Volatilitas Harga Saham Perusahaan Manufaktur - Linda Santioso; Yosevin Gloria Angesti (Jurnal Ekonomi, 2019)
The purpose of this study is to find out and analyze the influence of dividend policy, earning volatility, debt policy, growth asset and earning per share. The research method used was purposive sampling with a total sample of 35 manufacturing companies listed on the Indonesia Stock Exchange (IDX). This research was conducted using years of observation, namely 2015-2017. The type of data used is secondary data. Data is obtained from financial statements taken from www.idx.com. The data analysis method used is a descriptive statistical test, multicollinearity test, F test, t-test and test coefficient of determination. Testing the hypothesis in this study uses the t-test. The results of the study show that the dividend policy, earning volatility, debt policy and growth asset do not have a significant effect on share price volatility, while the earning per share has a significant negative effect on share price volatility.